Optimalisasi Peran DPRD dalam Pengawasan Keuangan Daerah - Sri Murni (Jurnal Akuntansi dan Bisnis, 2004)
The Objective of this paper is discussing how to optimizing the role oflegislative (DPRD) in controlling region’s finance. It will describe about introduction,concepts of region’s finance and management of region’s finance, budgeting andbudgeting cycle, oversight of region’s finance, role and function of legislative (DPRD),optimizing role of legislative in controlling region’s finance, future implication, andconclusion.